Gambaran Perilaku Orang Tua dalam Menjaga Kesehatan Gigi dan Mulut Anak Tunagrahita Tingkat SD – SMP di SLB Negeri 2 Padang - Aninda Putri Mulyani; Sri Ramayanti; Wulandani Liza Putri (Faculty of Dentistry Universitas Andalas, 2022)
Introduction: Children with special needs, especially in groups of mentally retarded has greater risk of poor oral hygiene. Mental retardation is a term to describe individuals with below-average general intellectual functioning. Mental retardation and lack of coordination in movement in mentally retarded cause them haven’t skills to clean their teeth and mouth independently so they tend to be guided and cared by their parents. Objective: to describe behaviour of parents in maintaining the oral health of mentally retarded children at SD – SMP levels in SLBN 2 Padang. Methods: This study was categorical descriptive quantitative with cross sectional design. The number of samples is 40 respondents. Data were collected by filling out a questionnaire on how to maintain oral and dental health in mentally retarded children. Results: This study showed the level of knowledge of parents as much as 60% in the high category, attitudes of parents as much as 67% in the good category, and practices of parents as much as 47.5% in the moderate category. Conclusion: The level of behaviour of parents in maintaining the dental and oral health of mentally retarded children at the SD – SMP level in SLBN 2 Padang is in the good category.